Progesterone and Allopregnanolone Rapidly Attenuate Estrogen-Associated Mechanical Allodynia in Rats with Persistent Temporomandibular Joint Inflammation - Hornung, Rebecca S.; Benton, William L.; Tongkhuya, Sirima; Uphouse, Lynda; Kramer, Phillip R.; Averitt, Dayna Loyd (Frontiers in Integrative Neuroscience, 2020)
Temporomandibular joint disorder (TMD) is associated with pain in the joint (TMJ) and muscles involved in mastication. TMD pain dissipates following menopause but returns in some women undergoing estrogen replacement therapy. Progesterone has both anti-inflammatory and antinociceptive properties, while estrogen’s effects on nociception are variable and highly dependent on both natural hormone fluctuations and estrogen dosage during pharmacological treatments, with high doses increasing pain. Allopregnanolone, a progesterone metabolite and positive allosteric modulator of the GABAA receptor, also has antinociceptive properties. While progesterone and allopregnanolone are antinociceptive, their effect on estrogen-exacerbated TMD pain has not been determined. We hypothesized that removing the source of endogenous ovarian hormones would reduce inflammatory allodynia in the TMJ of rats and both progesterone and allopregnanolone would attenuate the estrogen-provoked return of allodynia. Baseline mechanical sensitivity was measured in female Sprague Dawley rats (150-175 g) using the von Frey filament method followed by a unilateral injection of complete Freund’s adjuvant (CFA) into the TMJ. Mechanical allodynia was confirmed 24 hours later; then rats were ovariectomized or received sham surgery. Two weeks later, allodynia was reassessed and rats received one of the following subcutaneous hormone treatments over 5 days: a daily pharmacological dose of estradiol benzoate (E2; 50 µg/kg), daily E2 and pharmacological to sub-physiological doses of progesterone (P4; 16 mg/kg, 16 µg/kg, or 16 ng/kg), E2 daily and interrupted P4 given every other day, daily P4, or daily vehicle control. A separate group of animals received allopregnanolone (0.16 mg/kg) instead of P4. Allodynia was reassessed one hour following injections. Here we report that CFA-evoked mechanical allodynia was attenuated following ovariectomy and daily high E2 treatment triggered the return of allodynia, which was rapidly attenuated when P4 was also administered either daily or every other day. Allopregnanolone treatment, whether daily or every other day, also attenuated estrogen-exacerbated allodynia within one hour of treatment, but only on the first treatment day. These data indicate that when gonadal hormone levels have diminished, treatment with a lower dose of progesterone may be effective at rapidly reducing the estrogen-evoked recurrence of inflammatory mechanical allodynia in the TMJ.